The thrust zone of the Ligurian Penninic basal contact (Monte Fronté, Ligurian Alps, Italy). Issue 1 (4th November 2016) - Maino, Matteo; Seno, Silvio
ABSTRACT: This paper presents a geological map and interpretative cross-sections, which illustrate the structure of a major fault zone of the Alps, that is, the Ligurian segment of the Penninic Basal Contact (PBC), which led to the emplacement of the orogenic wedge onto the European crust. Chaotic deposits, whose origin is debated, characterize the footwall of this complex thrust zone. The lower part of the sequence containing chaotic deposits consists of low deformed paraconglomerates and exotic megablocks embedded with turbidites. Conversely, the highly deformed upper part of the sequence englobes fragments of substratum-derived succession and is bounded by thrust planes. The nature of these chaotic deposits suggests an origin by gravitational processes related to the unstable front of the advancing wedge associated with offscraping of tectonic slices during the thrusting of allochtonous nappes along the PBC thrust zone.